2000
DOI: 10.1002/1099-1565(200007/08)11:4<243::aid-pca520>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of triterpenes friedelan-3-?-ol and friedelin in Maytenus aquifolium by high-resolution gas chromatography and high- temperature capillary gas chromatography

Abstract: The quantitative analysis of the pentacyclic triterpenes friedelan‐3‐β‐ol and friedelin by high‐temperature capillary gas chromatography (HT‐CGC) and high‐resolution gas chromatography (HRGC) is described. These compounds are markers of Maytenus aquifolium and M. ilicifolium (Celastraceae), plants which show anti‐ulcer activity and which are used medicinally in Brazil under the name “espinheira santa”. HT‐CGC was more efficient than conventional HRGC for the quantitative evaluation of triterpenes in the hexane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Phytchemical studies carried out in plants of the genus Maytenus revealed the triterpenes friedeline and friedelol can be considered chemosystematic markers of the genus (NOSSACK et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Phytchemical studies carried out in plants of the genus Maytenus revealed the triterpenes friedeline and friedelol can be considered chemosystematic markers of the genus (NOSSACK et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The pharmacological potential of cork lies in its low molecular weight components, but to date, only its friedelin and friedelin derivatives have been studied. [157][158][159][160] Friedelin and related compounds extracted from other natural products have been studied 76,78,157,161,162 and reported to show antioxidant, antistaminic, antiulcer, 159 anti-inflammatory 86 or even anticancer effects. 80 Betulinic acid, a triterpene like friedelin has been studied 163 for prevention and treatment of cancer and HIV infection.…”
Section: Pharmacological Potentialmentioning
confidence: 99%
“…[157][158][159][160] Friedelin and related compounds extracted from other natural products have been studied 76,78,157,161,162 and reported to show antioxidant, antistaminic, antiulcer, 159 anti-inflammatory 86 or even anticancer effects. 80 Betulinic acid, a triterpene like friedelin has been studied 163 for prevention and treatment of cancer and HIV infection.…”
Section: Pharmacological Potentialmentioning
confidence: 99%